Anxiety in and about Africa : multidisciplinary perspectives and approaches - Grant, Andrea, 1981-; Pringle, Yolana (Cambridge Centre of African Studies series., 2021)
"This volume demonstrates the richness of anxiety as an analytical lens within African studies. Contributors call attention to ways of thinking about African spaces-physical, visceral, somatic, and imagined-as well as time and temporality. Through a multidisciplinary approach, the volume also brings histories of anxiety in colonial settings into conversation with work on the so-called negative emotions in disciplines beyond history. While anxiety has long been acknowledged as able to unsettle colonial narratives, to reveal the vulnerability of the colonial enterprise, this volume shows it can equally unsettle related narratives in the contemporary moment, such as those of sustainable development, migration, sexuality, and democracy. These essays therefore highlight the need to take emotions seriously as contemporary realities with particular histories that must be carefully mapped out"--